Binuclear titanium complexes coordinated by rigid p‐phenylene linked bis‐β‐carbonylenamine: Synthesis, structure, ethylene polymerization and copolymerization with 1, 5‐hexadiene. (15th May 2020) - Li, Jian; Wang, Liwei; Qin, Yawen; You, Qingliang; Li, Tingcheng; Sun, Lang; Li, Xiangdan; Xie, Guangyong
Abstract : Binuclear complexes for olefin polymerization have attracted great attention due to their unique catalytic properties compared with their mononuclear counterparts. Here a series of p ‐phenylene‐bridgedbis‐β‐carbonylenamine ligands and their binuclear Ti complexes Ti 2 L 1 –Ti 2 L 3 were prepared and characterized by 1 H NMR, 13 C NMR, Fourier transform infrared spectroscopy, and elemental analysis. The binuclear complex Ti 2 L 3 bearing an octylthio sidearm was further investigated by single‐crystalX‐ray diffraction, which revealed that the ligand was of β‐imino enol form, with one titanium atom ligated with six other atoms, forming a deformed octahedral configuration. Furthermore, the ligand in Ti 2 L 3 adopted a cis configuration, which was different from the trans configuration of its m ‐phenylene‐bridged derivatives. These binuclear complexes (Ti 2 L 1 –Ti 2 L 3 ) could catalyze ethylene polymerization and copolymerization with 1, 5‐hexadiene(1, 5‐HD) efficiently under modified methylaluminoxane activation. Compared with the mononuclear complex TiL 5, the binuclear catalysts were thermally more stable and showed higher activity for ethylene polymerization at higher temperatures. The activity of these titanium complexes for the copolymerization of ethylene with 1, 5‐HD were over 10 6 g/mol Ti.h.atm, almost twice as high as for homopolymerization. Compared with the mononuclear analogue TiL 5 and the m ‐substituted binuclear derivative Ti 2 L 4, binuclear catalyst Ti 2 L 2 showed higher activity and insertion rate of the comonomer. The activity of Ti 2 L 2 was two to three times higher than that of TiL 5 and Ti 2 L 4, indicating that p‐ substituted binuclear catalysts generate clear bimetallic synergistic effect for the copolymerization of ethylene and 1, 5‐HD. Meanwhile, 1, 5‐HD takes 1, 3‐cyclopentyl form in the polymer by 1, 3‐insertion. The copolymer prepared by binuclear catalysts had higher molecular weight and wider molecular weight distribution than that prepared by the mononuclear catalyst. Abstract : The p ‐phenylene‐bridgedbis‐β‐carbonylenamine ligated binuclear titanium complexes Ti 2 L 1 –Ti 2 L 3 were synthesized, characterized, and used to catalyze ethylene polymerization and ethylene/1, 5‐hexadiene(1, 5‐HD) copolymerization with moderate to high activity, high thermal stability, and high incorporation of 1, 5‐HD comonomer.